Are post-Soviet republics ready for the new public management? The case of educational modernization in Kazakhstan. Issue 2 (2nd March 2015) - Monobayeva, Agipa; Howard, Cosmo
Abstract : Purpose: – Since the collapse of the USSR, former Soviet republics have embarked on public service modernization, in most instances drawing on internationally dominant new public management (NPM) principles. Are post-Soviet republics ready for these administrative prescriptions? The paper aims to discuss these issues. Design/methodology/approach: – This paper discusses Kazakhstan's experience with the implementation of NPM through a qualitative case study of the country's adoption of the European Bologna higher education reforms. Findings: – While implementation of the NPM-inspired Bologna program has produced significant achievements, there are also gaps and shortcomings. These are due to a remnant Soviet administrative practices including strong control by educational ministries, as well as incompatible organizational cultures and a tendency toward superficial formalism in the implementation process. Research limitations/implications: – NPM tends to be introduced in a top-down fashion as a taken-for-granted component of state transformation, without sufficient attention to the capacities, cultures and systems required for effective and accountable performance-driven administrative reform. Originality/value: – Kazakhstan's experience provides crucial insights into the governance structures, professional cultures and managerial capacities required for successful implementation of NPM in post-Soviet states.